Resistência varietal de morangueiro aos pulgões Cerosipha forbesi (Weed) e Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae) - Guimarães, Amanda Gonçalves; Soares, Marcus Alvarenga; de Andrade Júnior, Valter Carvalho; da Silva, Isabel Moreira; Guimarães, Cíntia Gonçalves; Pires, Evaldo Martins (EntomoBrasilis, 2018)
Resumo. A identificação de picos populacionais de pragas e a seleção de genótipos resistentes ajudam a definir o momento do controle e reduzir a aplicação de inseticidas. O objetivo deste estudo foi avaliar aresistência varietal de seis cultivares de morangueiro (Aromas, Campinas, Dover, Festival, Oso Grande e Toyonoka) ao ataque de Cerosipha forbesi (Weed)e Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae). A presença dos pulgões nas plantas foi avaliada semanalmente por contagem direta em três folíolos por planta, durante cinco meses (Fevereiro a Junho de 2012). Março apresentou a maior densidade de ambas espécies de pulgões, com redução populacional nos meses próximos ao inverno. As cultivares Campinas, Toyonoka e Dover tiveram maior incidência de C. forbesi, e Campinas e Toyonoka foram também mais atacadas por C. fragaefolii. As cultivares Festival, Aromas e Oso Grande apresentaram menores infestações de ambas as espécies, tendo potencial para serem utilizadas em programas de melhoramento visando à resistência ao ataque de C. forbesi e C. fragaefolii. Varietal resistance of strawberry to aphids Cerosipha forbesi (Weed) and Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae) Abstract. The identification of peak populations of pests and the selection of resistant genotypes help to define the timing of control and to reduce the frequency of insecticide application. The objective of this study was to evaluate varietal resistance of six strawberry cultivars (Aromas, Campinas, Dover, Oso Grande and Toyonoka) to the attack of Cerosipha forbesi (Weed) and Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae). Attack of the aphids was evaluated on a weekly basis by direct counting in three leaflets per plant for five months (February to June 2012). March presented higher densities of both aphids species, with population reductions in months closer to the winter. The cultivars Campinas, Toyonoka, and Dover had higher incidence of C. forbesi, and Campinas and Toyonoka were also more attacked by C. fragaefolii. The cultivars Festival, Aromas, and Oso Grande presented lower infestation of both aphids species, and hold potential to be used in breeding programs aiming resistance to attack of C. forbesi and C. fragaefolli.